In Hypertrophic Cardiomyopathy, the Spatial Peaks QRS‐T Angle Identifies Those With Sustained Ventricular Arrhythmias. Issue 8 (13th May 2016) - Cortez, Daniel; Graw, Sharon; Mestroni, Luisa
ABSTRACT: Background: The spatial peaks QRS‐T (SPQRS‐T) angle differentiates hypertrophic cardiomyopathy (HCM) patients from controls. Increased angle confers arrhythmia risk in other populations. Hypothesis: We predict that the SPQRS‐T angle will identify HCM patients with sustained ventricular arrhythmias (VAs) and those with New York Heart Association class III/IV heart failure. Methods: Corrected QT interval, QRS duration, and SPQRS‐T angle were assessed in HCM patients with VAs (>30 seconds) and those without VAs. Results: One hundred HCM patients (mean age, 32.7 ± 17.2 years) were assessed. Twenty patients had VAs. The corrected QT interval identified VA ( P = 0.018) and at 460 ms gave positive and negative predictive values of 28.6% and 83.3%, respectively, and an odds ratio of 2.0 (95% confidence interval: 0.7‐5.6). The SPQRS‐T angle differentiated VA from no VA ( P < 0.001) and at 124.1 degrees gave positive and negative predictive values and an odds ratio of 36.7%, 96.1%, and 14.2 (95% confidence interval: 3.1‐65.6), respectively. Conclusions: The SPQRS‐T angle best differentiated patients with VAs.